A reliable peer-to-peer storage framework based on virtual peers model. (3rd March 2020) - He, Hong
Peer-to-peer (P2P) networks have become popular applications due to their ease of communication and resource sharing patterns in unfixed network infrastructures. However, typical P2P systems often suffer from the problem of unreliable network transferring and unstable availability of data files. In this paper, we propose a novel P2P-based storage framework, which introduces a set of virtual peers to improve the reliability of networking transferring and storage by using the networking coding technology. Also, we present a detailed theoretical analysis on storage performance and management cost, which indicates that the proposed framework is capable of achieving better tradeoffs between reliability and efficiency. To evaluate the effectiveness of the proposed framework, extensive experiments are conducted in a realworld P2P storage platform, and the experimental results show that our P2P storage framework outperforms the existing solutions in terms of many performance metrics, including data availability, resource utilisation, and communication cost.